Intervensi Berbasis Produk Pangan Lokal untuk Meningkatkan Kadar Hemoglobin pada Remaja Putri Anemia di Indonesia: Tinjauan Sistematis: Local Food-Based Interventions to Improve Hemoglobin Levels Among Anemic Female Adolescents in Indonesia: A Systematic Review - Fayasari, Adhila; Nilansari, Anis Febri; Pambudi, Brevi Istu (Universitas Airlangga, 2025)
Background: Anemia is prevalent among female adolescents. Food-based approaches have been developed to improve hemoglobin levels. However, their effectiveness has not been thoroughly evaluated yet. Objectives: This review aims to analyze the effectiveness of food-based interventions, either alone or in combination with iron supplementation, in improving hemoglobin (Hb) levels among anemic female adolescents in Indonesia. Methods: This review was conducted using the PICO framework and followed the PRISMA guidelines. Articles were retrieved from PubMed, Scopus, Google Scholar, Garuda, and ResearchGate. Eligible studies included experimental designs with control groups involving female adolescents aged 10-18 years, published between 2014 and 2024. Interventions consisted of food-based products, while comparators included iron tablets alone or in combination with a placebo. Hemoglobin levels were the primary outcome assessed. Discussions: Of the 1,142 studies identified, 13 met the inclusion criteria and were included in a systematic review. Commonly used dietary interventions included iron-rich food sources, such as fish and nuts, and vitamin C-rich food sources, including dates and guava. Local food-based interventions were associated with increases in hemoglobin levels, with reported Hb improvements ranging from 0.8 to 2.7 g/dL. Several studies demonstrated statistically significant differences both within intervention groups and between intervention and control groups. Although effect sizes varied, most interventions showed meaningful benefits. Conclusions: Local food-based nutrition interventions in Indonesia, particularly those combed with iron supplementation, consistently improve hemoglobin levels and show promise as effective strategies to reduce anemia among female adolescents.